Understanding Identity Negotiation of Parkinson's Disease and Occupational Engagement Using Narrative Inquiry. (3rd April 2022) - Sheldrake, Elena; McGrath, Colleen; Laliberte Rudman, Debbie; Holmes, Jeff
Abstract: Aims: Many older adults with Parkinson's disease experience challenges negotiating identity, often with negative implications for wellbeing. This study explores how older adults with Parkinson's disease negotiate identity post-diagnosis, specifically addressing how they recount their management of identity and its impact on their occupational engagement. Methods: Using a constructivist narrative approach, three participant sessions were conducted with five older adults with Parkinson's disease. Line-by-line and thematic coding was completed. Results: Three major themes emerged across narratives including: (a) Attempts to convey, maintain, and negotiate identity; (b) Resisting a disabled identity and (c) The centrality of occupation and social roles in negotiating identity. Conclusion: Common themes of personal and social identity that threaten or support an older adult with PD's decisions about occupational engagement were identified. Results of this study can be used by occupational therapists to better understand the influence of identity on occupational engagement.